Site-directed spin labeling of 2′-amino groups in RNA with isoindoline nitroxides that are resistant to reduction1. Issue 66 (25th August 2015) - Saha, Subham; Jagtap, Anil P.; Sigurdsson, Snorri Th.
<x xml:space="preserve">Abstract</x> 2'-Amino groups in RNA were selectively spin labeled with reductively stable isoindoline nitroxides through a high-yielding reaction with aromatic isothiocyanates.